2016
DOI: 10.1074/jbc.m116.728006
|View full text |Cite
|
Sign up to set email alerts
|

Der f 34, a Novel Major House Dust Mite Allergen Belonging to a Highly Conserved Rid/YjgF/YER057c/UK114 Family of Imine Deaminases

Abstract: The high prevalence of house dust mite (HDM) allergy is a growing health problem worldwide, and the characterization of clinically important HDM allergens is a prerequisite for the development of diagnostic and therapeutic strategies. Here, we report a novel HDM allergen that belongs structurally to the highly conserved Rid/YjgF/YER057c/UK114 family (Rid family) with imine deaminase activity. Isolated HDM cDNA, named der f 34, encodes 128 amino acids homologous to Rid-like proteins. This new protein belongs to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 47 publications
(56 reference statements)
0
19
0
Order By: Relevance
“…Interest on UK114 has also been recently stimulated by the identification of Der f 34, which is a major allergen of house dust mite ( Dermatophagoides farinae ). This homolog of UK114 is endowed with RidA activity [ 37 ]. Der f 34 and a component of the spores of the fungus Aspergillus fumigatus cross-react with IgE from patients allergic to indoor allergens, suggesting that members of the RidA protein family may represent important pan-allergens that are conserved across different organisms [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interest on UK114 has also been recently stimulated by the identification of Der f 34, which is a major allergen of house dust mite ( Dermatophagoides farinae ). This homolog of UK114 is endowed with RidA activity [ 37 ]. Der f 34 and a component of the spores of the fungus Aspergillus fumigatus cross-react with IgE from patients allergic to indoor allergens, suggesting that members of the RidA protein family may represent important pan-allergens that are conserved across different organisms [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Members of the RidA subfamily from bacteria, plants, archaea, house dust mite, and humans had activity that was indistinguishable from the S . enterica protein when tested in vivo and in vitro [ 7 , 9 , 22 , 24 ]. Significantly, high resolution structures of more than twenty RidA homologs had been determined prior to any biochemical information on their function [ 1 , 15 , 25 30 ], many of which exist as Protein Data Bank entries yet to be published.…”
Section: Introductionmentioning
confidence: 99%
“…We found that 113 spots possessed IgE‐binding capacity in 40 HDM‐allergic patients and that the IgE‐binding frequency of the spots ranged from 2.5% (1/40) to 85.0% (34/40) (Ref. and unpublished data). Two spots were identified as a major HDM allergen, Der f 2, with 77.5% (31/40) and 65.0% (26/40) IgE‐binding frequency (Figure A,B).…”
Section: Resultsmentioning
confidence: 84%
“…Two‐dimensional immunoblotting analysis in the allergenome study was carried out using plasma samples from 40 patients allergic to HDM (Ref. and unpublished data). Proteins from D. farinae extract were loaded onto 2D sodium lauryl sulfate (SDS)‐polyacrylamide gel, followed by immunoblotting with HDM‐allergic patients' plasma as described previously .…”
Section: Methodsmentioning
confidence: 99%